Trajectories of depression symptoms over time differ by APOE4 carriership in older adults with type 2 diabetes: Neuropsychiatry and behavioral neurology/Assessment/Measurement of neuropsychiatric/Behavioral and psychological symptoms. (7th December 2020) - Lavie, Inbar; Schnaider Beeri, Michal; Berman, Yuval; Schwartz, Jonathan M.; Soleimani, Laili; Heymann, Anthony; Ravona‐Springer, Ramit
Abstract: Background: APOE‐ε4 is a strong and consistent risk gene for Alzheimer's disease (AD). Depression and depressive symptoms have been shown to precede AD and are highly prevalent in older adults with type 2 diabetes (T2D). However, the relationship of APOE‐ε4 with depression has rarely been investigated T2D. We examined whether trajectories of depression symptoms over time differ by APOE‐ε4 carriership in older adults with T2D. Method: Participants (n=754 (99 APOE‐ε4 carriers; 13.1%) were initially cognitively normal individuals from the Israel Diabetes and Cognitive Decline (IDCD) study who underwent evaluations of depression approximately every 18 months using the 15‐item version of the Geriatric Depression Scale (GDS) and the depression subscale of the Neuropsychiatric Inventory (NPI). We used Hierarchical Linear Mixed Models (HLMM) that modeled the effects of APOE status on repeated GDS and NPI depression scores adjusting for demographic (Model 1), and adding cardiovascular risk factors (Model 2) and global cognition (Model 3). Result: Participants' mean age was 73 (SD=4.7); 38% female. In comparison to non‐carriers, APOE‐ε4 carriers had a lower mean GDS scores (β=‐0.46, p=0.018; Plot 1) and lower NPI‐depression scores (β=‐0.170, p=0.038; Plot 2) throughout all study follow period, but the groups did not differ in the slope of change over time in GDS (β=‐0.005 for interaction of APOE with time, p=0.252) or NPI‐depression (β=‐0.001, p=0.994) scores. Additional adjustment for cardiovascular risk factors and global cognition did not alter these results. Conclusion: In older adults with T2D, APOE‐ε4 carriers have consistently lower depression scores in successive measurements. The lack of difference between the groups' slopes over time suggests that APOE‐ε4 (or lack of) does not have a progressive effect on depression or its underlying pathology. APOE‐ε4 carriers may be less susceptible to depression.